Synthesis and characterization of Aspartame and Neotame-encapsulated PLGA-TPGS nanoparticles and their modulatory effects on acetylcholinesterase gene expression in male rats - Mohammed, A. J.; Al-Awadi, H. K.; Al-Shukri, H. H. K. (Regulatory Mechanisms in Biosystems, 2025)
This study investigates the synthesis, characterization, and biological impact of novel nanoparticle formulations of two artificial sweeteners Aspartame and Neotame encapsulated in PLGA-TPGS (poly(lactic-co-glycolic acid)-D-α-tocopheryl polyethylene gly col 1000 succinate) matrices. Nanoparticles were developed using a combination of emulsification, sonication, and solvent evapor a tion techniques, followed by detailed physicochemical characterization via UV–Vis spectroscopy, SEM, TEM, DLS, FTIR, and EDX. The in vitro release profiles demonstrated sustained release patterns for both Aspartame (ASPNPs) and Neotame (NEONPs) formulations compared to their free forms. In vivo experiments using male Wistar rats assessed the effects of these sweeteners and their nanoformulations on acetylcholinesterase (AChE) gene expression. Free forms of Aspartame and Neotame significantly el e vated AChE gene expression, suggesting potential neurotoxic effects, while ASPNPs and NEONPs mitigated this elevation, indica t ing a protective role of nanoencapsulation. These findings highlight the potential of PLGA-TPGS nanoparticle systems in reducing the neurotoxic effects associated with chronic intake of synthetic sweeteners through controlled release and improved bioavailability.